Effect of Growing Media on Seed Germination and Seedling Growth of Chili (Capsicum Annuum L.) : Effect of Growing Media on Chili Seed Germination and Seedling Growth - Shakhidar, Md Sazu; Akter, Nasima; Muhammad Abdus, Sobahan (SAARC Journal of Agriculture, 2025)
Suitable growing media is considered a basic requirement to get the maximum germination and growth. So, the present investigation was carried out at Mominpur Farmers Hub (name of model), Rangpur Sadar Upazila during February-March, 2023 to investigate the effect of growing media on germination percentage, germination emergence percentage, shoot length, shoot fresh weight, root length, root fresh weight, leaf number, shoot length vigor index, root shoot ratio of chili under open field condition. The experiment was sequenced according to Completely Randomized Design in three replicates. Five different growing media namely soil + sand, cocopeat, soil + sand + cocopeat, vermicompost + cocopeat, and vermicompost + soil + sand was used in the experiment. The results obtained from this study showed that the maximum germination percentage (94%), shoot length (9.62 cm), shoot fresh weight (7.16 g), root length (3.09 cm), root fresh weight (1.93 g), leaf number (7.02) and shoot length vigor index (1194.74%) were recorded when the seed was growing in the cocopeat. The findings of this study recommend the use of cocopeat as a growth media for raising nurseries by farmers as it had a significant positive effect on seed germination and plant growth parameters of seedlings that lead to increased production of chili. SAARC J. Agric., 22(2): 289-301 (2024)